HISTORITAS DAN OTENTISITAS AL-QUR'AN (STUDI KOMPARATIF ANTARA ARTHUR JEFFERY DENGAN MANNA' AL- QATHAN) - Nur Fahrizi; Muhammad Zubir (Universitas Muhammadiyah Surakarta, 2022)
The study of the Qur'an, especially the historicity of the Qur'an, has attracted the attention of the world both among Muslims and non-Muslims. Therefore, the author is interested in bringing up this title because it is very relevant and will continue to be a discussion that arises from time to time. The research method used is the type of library research (Library Research). While this research is descriptive comparative. The results of the research that the authors found show that First: Arthur Jeffery Criticizing the belief of Muslims only believing in the history of the revelation of the Qur'an is a classical and unscientific reason, the compilation of the Ottoman Mushaf contained in it political issues of Usman, and the Qur'an not perfect to represent the previous heavenly books. Second, Manna' al-Qattan's rebuttal to the Historicity and Authenticity of the Qur'an, namely: The history of the revelation of the Qur'an is not an orthodox reason as in his book explains that if the Prophet wanted power for himself, he could attribute the Qur'an to to himself directly, because it is enough to elevate his position and make people submit to his power. Usman made the manuscripts not for political reasons but because of his concern about disputes that would occur if they were with different manuscripts. And finally, the Qur'an The Qur'an is a complement to the previous books so that it can cause divisions between Muslims. The similarity between one book and the previous books is a natural thing. Third: There is no definite reason to accept the argument from Arthur Jeffery's view because it is unable to show valid evidence. Jeffery's analysis is a historical study that still invites a number of criticisms. On the side of Manna' al-Qattan, linguistic analysis and based on the history of qira'ah in a mutawatir manner, shows the authenticity of the Surah al-Qur'an that exists today.